2022
DOI: 10.21093/ijeltal.v6i2.1050
|View full text |Cite
|
Sign up to set email alerts
|

What’s Covid19 Got to Do with My Communicative Competence? Self-reflections of Pre-service English Language Teachers in Turkey

Abstract: With the emergence of the COVID-19 pandemic, nearly all theoretical and practical classes and methods of assessment had to be delivered on digital platforms. This paper reports the use of task-based assessment of the communicative competence of first-year pre-service English language teachers. The aim was to explore the role of the platform where the tasks were held on the students’ self-assessment of their spoken performances. The participants (n=50) evaluated their linguistic, discourse, strategic and sociol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…They felt that reflective activity helps them tackle problems they had found in teaching practicum. Doing reflective activities turned out to be a positive way to perform well in teaching practicum (Geckin, 2022). Furthermore, the help-seeking in this study found that the tutor's role had a higher score than the family role.…”
mentioning
confidence: 59%
“…They felt that reflective activity helps them tackle problems they had found in teaching practicum. Doing reflective activities turned out to be a positive way to perform well in teaching practicum (Geckin, 2022). Furthermore, the help-seeking in this study found that the tutor's role had a higher score than the family role.…”
mentioning
confidence: 59%
“…In addition to the negative perceptions of prospective teacher students, such as the lack of an interactive or passive environment, a lack of technological equipment and internet connection issues, unpleasant compared to face-to-face educational environments, and a lack of pe, the existence of a pandemic has indirectly affected the decline in the quality of prospective teacher students, especially in communicating both conveying subject matter and responding to questions from students (Geçkin, 2022;Makawawa et al, 2021;Smith & Schlaack, 2021). The support of tertiary institutions, particularly lecturers, can help students increase their abilities by using a variety of programs or lecture materials.…”
Section: Table 3 Description Of Thementioning
confidence: 99%
“…It illustrated that the increasing of cognitive domain by applying virtual discussion was not always followed by the increasing of affective domain. Geçkin (2022), Hafeez et al (2022), Laili & Nashir (2021), Madhuwanthi et al (2021), Saleh et al (2021), andSanoto, (2021) are also some scholars who discussed the impact of online learning delivery. The scholars' studies can be a reference of the science development as a comparison for the future studies.…”
Section: Introductionmentioning
confidence: 99%